Loss of PTEN-Induced Kinase 1 Regulates Oncogenic Ras-Driven Tumor Growth By Inhibiting Mitochondrial Fission - Zhu, Dantong; Han, Fengtong; Sun, Liuke; Agnihotri, Sandeep K.; Hu, Ying; Büeler, Hansruedi (Frontiers in Oncology, 2022)
Mitochondrial metabolism and dynamics (fission and fusion) critically regulate cell survival and proliferation, and abnormalities in these pathways are implicated in both neurodegenerative disorders and cancer. Mitochondrial fission is necessary for the growth of mutant Ras-dependent tumors. Here, we investigated whether loss of PTEN-induced kinase 1 (PINK1) - a mitochondrial kinase linked to recessive familial Parkinsonism - affects the growth of oncogenic Ras-induced tumor growth in vitro and in vivo. We show that RasG12D-transformed embryonic fibroblasts (MEFs) from PINK1-deficient mice display reduced growth in soft agar and in nude mice, as well as increased necrosis and decreased cell cycle progression, compared to RasG12D-transformed MEFs derived from wildtype mice. PINK1 re-expression (overexpression) at least partially rescues these phenotypes. Neither PINK1 deletion nor PINK1 overexpression altered Ras expression levels. Intriguingly, PINK1-deficient Ras-transformed MEFs exhibited elongated mitochondria and altered DRP1 phosphorylation, a key event in regulating mitochondrial fission. Inhibition of DRP1 diminished PINK1-regulated mitochondria morphological changes and tumor growth suggesting that PINK1 deficiency primarily inhibits Ras-driven tumor growth through disturbances in mitochondrial fission and associated cell necrosis and cell cycle defects. Moreover, we substantiate the requirement of PINK1 for optimal growth of Ras-transformed cells by showing that human HCT116 colon carcinoma cells (carrying an endogenous RasG13D mutation) with CRISPR/Cas9-introduced PINK1 gene deletions also show reduced mitochondrial fission and decreased growth. Our results support the importance of mitochondrial function and dynamics in regulating the growth of Ras-dependent tumor cells and provide insight into possible mechanisms underlying the lower incidence of cancers in Parkinson’s disease and other neurodegenerative disorders.